2009
DOI: 10.1111/j.1600-0838.2008.00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Organized youth sport as a predictor of physical activity in adulthood

Abstract: The aim of this study was to examine whether early and sustained organized youth sport during childhood and adolescence predicts the frequency of leisure-time physical activity (PA) at age 23 years. A 10-year longitudinal study of 630 adolescents was conducted. Data were collected from these participants eight times from the ages of 13 to 23 years and were analyzed by analysis of variance and regression. There was a high degree of consistency in participation in organized youth sport in terms of reporting to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
149
1
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(169 citation statements)
references
References 30 publications
10
149
1
9
Order By: Relevance
“…In these settings for self-organized physical play and sports, children from ethnic minority backgrounds are able to participate to the same extent as children. However, as the generally high level of participation in club sports among Scandinavian children has been found to be important to children's participation, integration and network building in local communities (Anderson, 2008;Ibsen & Ottesen, 2005;Pestoff, 2009) and may be important to their physical activity level later in life (Kjønniksen et al, 2009;Ottesen & Skjerk, 2006) it is problematic that this study found children from immigrant backgrounds had lower participation rates in club sports. This finding is in line with numerous Danish (Ibsen, 2007;Nielsen & Ibsen, 2008;Lykkegaard, 2001) as well as international studies (Horne, Tomlinsin, & Whannel, 1999;DeKnop, Theboom, Van Engelan, & Van Puymbroeck, 1995;DeKnop, Theboom, Wittock, & DeMartelaer, 1996;Gajendra & Darby, 1994).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In these settings for self-organized physical play and sports, children from ethnic minority backgrounds are able to participate to the same extent as children. However, as the generally high level of participation in club sports among Scandinavian children has been found to be important to children's participation, integration and network building in local communities (Anderson, 2008;Ibsen & Ottesen, 2005;Pestoff, 2009) and may be important to their physical activity level later in life (Kjønniksen et al, 2009;Ottesen & Skjerk, 2006) it is problematic that this study found children from immigrant backgrounds had lower participation rates in club sports. This finding is in line with numerous Danish (Ibsen, 2007;Nielsen & Ibsen, 2008;Lykkegaard, 2001) as well as international studies (Horne, Tomlinsin, & Whannel, 1999;DeKnop, Theboom, Van Engelan, & Van Puymbroeck, 1995;DeKnop, Theboom, Wittock, & DeMartelaer, 1996;Gajendra & Darby, 1994).…”
Section: Discussionmentioning
confidence: 68%
“…However in general it is important to use such direct objective measures because questionnaire measures have been found to be very unreliable measures of the highly sporadic physical activities of children. In contrast questionnaire methods seems to provide valid information on whether children participate in club-organized sports as it is very clear to children and their parents whether they are members of a sports club and whether they participate in sports club activities (Kjønniksen et al, 2009). This study was limited by only including 60 children from other ethnic backgrounds than Danish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of boys enrolled in sport clubs that involve high-intensity exercise (e.g., football, basketball, bicycling) is clearly higher than the number of girls (Vilhjalmsson and Kristjansdottir 2003;Borraccino et al 2009). This gender gap in involvement in sports translates into sex differences in the number of hours per week individuals spend doing exercise not only in childhood, but also in adulthood (Kjønniksen et al 2009). Boys and girls also appear to have different motivations for enrolling in a youth sport club: boys tend to report engaging in physical activities for the sake of competition and in order to demonstrate their abilities (male-oriented features); while girls tend to report exercising for health reasons, for social reasons, or to improve their appearance (female-oriented features) (Vilhjalmsson and Kristjansdottir 2003).…”
Section: Physical Activitymentioning
confidence: 99%
“…In contrast, studies only rarely focus on the student population, with a few of them demonstrating that although student interests have shifted from team to individual sports over the last decades (20), students still perceive sports activity as a positive value (21), which is evident from a rather high percentage of students who perform non-organised sports, thus sports activities in their free time (22), and would at the same time require some adaptation of the existing sports programs to suit them better (23,24 (1). It is worthwhile noting that the organisation of voluntary sports activities in Slovenia is similar to that in Scandinavian countries (7,26); apart from the extra-curricular school programs, organised sports activities for children are usually being organised by sports clubs, which in Slovenia are members of national sports associations. This is in contrast with the situation in the United States, where the majority of voluntary sports activities are organised by schools and universities.…”
Section: Introductionmentioning
confidence: 99%